Fundamental Ecumenics Revisited: A Near-Forgotten Intellectual Framework as a Toolkit for the Mid-Twenty-First Century - Hollander, Aaron T. (Journal of ecumenical studies, 2021)
During the 1970's, at the Catholic Ecumenical Institute of Münster, a group of scholars strove to theorize the human processes of understanding, communication, identification, and institutionalization that animate (and all too often compromise) ecumenical dialogue. The Münster group, led by Peter Lengsfeld, published Ökumenische Theologie: Ein Arbeitsbuch in 1980. This work was ahead of its time, yielding a wealth of resources for interpreting the entanglement of religious communities with one another and the epistemological force of those communities' oppositional identities. The Arbeitsbuch, however, was met upon publication with indifference or hostility in its own context and has received nearly no attention outside of Germany. This essay argues that the interpretive apparatus pioneered by Lengsfeld's working group—synthesized by John D'Arcy May as "fundamental ecumenics"—offers rigorous and adjustable diagnostic tools commensurate with needs emerging in the mid-twenty-first century. After introducing the framework pioneered by Lengsfeld and his collaborators and assessing the criticisms and reassessments that it subsequently met in the German academy, the essay sketches the contours of a fundamental ecumenics reformulated for the contemporary North American context, aiming to revitalize the discipline for analyzing the dynamics and stakes of human division—whether within, between, or beyond religious traditions.